The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages It is impossible here to set out in detail schemes for these groups, and only the general lines can be indicated. It is worth while perhaps to re-iterate that a social security scheme which will provide financially for those permanently unable to earn their living is an absolute minimum requirement. This applies equally to those whose incapacity is due to the war, and those in whom it is due to other causes. Those who are prevented by physical or mental disability from contributing their full quota of work to the social effort, should be given every opportunity for engaging in some suitable occupation. They must be enabled to do light work for shorter hours in specially favourable conditions without financial loss, and special travelling facilities should be arranged for them, reserved compartments, guides, etc. Special consideration should also be given to the housing requirements of such people, especially the blind, crippled and tuberculous, without segregating them from normal society. For the totally unemployable, in addition to financial provision, there must be occupational, social and recreational centres which cater for their special needs, and every effort should be made to prevent the lives of these people from becoming a burden to themselves or their families. Two groups which present special difficulties are the mentally disabled and the delinquent. There is no universal prescription or general line of 18 15X/2/464/1